From bench to bedside: translating mesenchymal stem cell therapies through preclinical and clinical evidence - Patel, Jai Chand; Shukla, Meenakshi; Shukla, Manish (Frontiers in Bioengineering and Biotechnology, 2025)
Mesenchymal stem cells (MSCs) are emerging as a powerful tool in regenerative medicine due to their ability to differentiate into mesenchymal lineages, such as bone, cartilage, and fat, along with their low immunogenicity and strong immunomodulatory properties. Unlike traditional cell therapies that rely on engraftment, MSCs primarily function through paracrine signaling—secreting bioactive molecules like vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-β), and exosomes. These factors contribute to tissue repair, promote angiogenesis, and modulate immune responses in damaged or inflamed tissues. Recent studies have identified mitochondrial transfer as a novel therapeutic mechanism, where MSCs donate mitochondria to injured cells, restoring their bioenergetic function. This has expanded the therapeutic potential of MSCs to include conditions such as acute respiratory distress syndrome (ARDS) and myocardial ischemia. Clinically, MSCs have shown efficacy in diseases like graft-versus-host disease (GVHD), Crohn’s disease, and COVID-19. Trials such as REMODEL and REMEDY have demonstrated improved clinical outcomes, further validating MSC-based interventions. However, several challenges remain, including variability in cell potency, poor engraftment, and inconsistent results across clinical trials. Advances in genetic engineering such as CRISPR-modified MSCs and biomaterial scaffolds are being developed to enhance therapeutic efficacy and cell survival. Additionally, AI-driven platforms are being utilized to personalize MSC therapy and optimize cell selection. Innovative approaches like 3D bioprinting and scalable manufacturing are paving the way for more consistent and precise therapies. Moving forward, the integration of mechanistic insights with robust quality control and regulatory frameworks essential to translating MSC therapies from bench to bedside and ensuring their reliable application in clinical practice.